Depletion of Oxygen in the Bothnian Sea Since the Mid-1950s - Polyakov, Igor V.; Tikka, Kimmo; Haapala, Jari; Alkire, Matthew B.; Alenius, Pekka; Kuosa, Harri (Frontiers in Marine Science, 2022)
Glider observations conducted between 2016 and 2021 were combined with shipborne surveys from the 1950s through the 2010s to provide critically important information about changes in the Bothnian Sea. Particularly, we evaluated the rate of warming and freshening in several layers of the basin and showed that ocean warming of 0.3oC/decade in the upper 25m was sufficient to explain ~40% of the oxygen depletion since the mid-1950s. This depletion was driven by limited saturation of the surface mixed layer (SML), caused by warming and a (related) weakening of the surface oxygen flux during spring blooms. Below the SML, the role of warming in oxygen depletion decreased to less than 30%, whereas the role of freshening became increasingly important via establishing stronger stratification that reduced local ventilation across the basin’s halocline. The observed values in this study are not critical for the ecological system of the Bothnian Sea. However, the presented trends towards oxygen depletion should be considered as an early warning sign as future projections of the oxygen levels in the Bothnian Sea suggest further severe losses of the dissolved oxygen in the next decades. Thus, enhancement of both observational networks and the current physical and biogeochemical models is a high priority if we are to mitigate the potential impact of oxygen loss and develop a reliable monitoring system of the Bothnian Sea.